1997
DOI: 10.1523/jneurosci.17-09-02967.1997
|View full text |Cite
|
Sign up to set email alerts
|

Second Messengers, Trafficking-Related Proteins, and Amino Acid Residues that Contribute to the Functional Regulation of the Rat Brain GABA Transporter GAT1

Abstract: Recent evidence indicates that several members of the Na ϩ -coupled transporter family are regulated, and this regulation in part occurs by redistribution of transporters between intracellular locations and the plasma membrane. We elucidate components of this process for both wild-type and mutant GABA transporters (GAT1) expressed in Xenopus oocytes using a combination of uptake assays, immunoblots, and electrophysiological measurements of membrane capacitance, transportassociated currents, and GAT1-specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 57 publications
4
115
1
Order By: Relevance
“…5B, E). This rectification is characteristic of GAT-associated currents (Quick et al, 1997). In contrast, the sustained outward current increased at depolarizing values and reversed at Ϫ75 mV (Fig.…”
Section: Effects Of Gaba In Cultured X-organ Cellsmentioning
confidence: 83%
“…5B, E). This rectification is characteristic of GAT-associated currents (Quick et al, 1997). In contrast, the sustained outward current increased at depolarizing values and reversed at Ϫ75 mV (Fig.…”
Section: Effects Of Gaba In Cultured X-organ Cellsmentioning
confidence: 83%
“…To understand the extent of this influence, it is essential to understand the mechanisms underlying subcellular transporter trafficking. We and others have previously isolated transporter-containing synaptic-like vesicles that are potential mediators of transporter trafficking in axon terminals (10), and we have identified many signaling molecules that regulate subcellular transporter redistribution (12,14,15,22,24,28). In this report, by using a modified biotinylation assay to study GAT1 trafficking, (i) we defined an acutely recycling pool of GAT1 in cortical neurons that, in the basal state, comprises approximately one-third of total cellular GAT1; (ii) we measured the exocytosis rate (r exo ϭ 0.7 min Ϫ1 ) and the endocytosis rate (r endo ϭ 1.1 min Ϫ1 ) of acutely recycling GAT1 in the basal state; and (iii) we demonstrated that distinct transporter redistribution signals exert their effects by differentially regulating the recycling pool size or selectively uncoupling rates of exocytosis and endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the difference in sequence between A␤ (1-42) and A␤ (1-40) is only two residues of C terminus, A␤ (1-42) aggregates more rapidly than A␤ (1-40) (28). Like A␤ (1-42), A␤ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), a biologically active, hydrophobic fragment of A␤ (29), is also highly prone to aggregation (30). This subfragment could also reproduce the effect of A␤ (1-42) (data not shown).…”
Section: A␤ Attenuates Glutamatergic Neurotransmission In Neuro-mentioning
confidence: 93%
“…the neuronal glutamate transporter EAAC1 expressed in C6 glioma (21), serotonin transporters expressed in HEK293 cells (33), the ␥-aminobutyric acid transporter GAT1 expressed in Xenopus oocytes (34), and dopamine transporters expressed in PC12 cells (35), it is also possible that the A␤ effect is achieved by an increase in GLAST proteins on the cell surface. This possibility was addressed by a membrane-impermeant biotinylation assay.…”
Section: A␤ Attenuates Glutamatergic Neurotransmission In Neuro-mentioning
confidence: 99%